Association of fatty acid desaturase 2 gene polymorphism (rs28456) with susceptibility to bipolar disorder in the Turkish population: A case-control study - Pirim Dilek; Gümüş Ceren; Boztepe Esra; Akdağ Emine Merve; Şirin Hande (Archives of Biological Sciences)
The FADS2 gene encodes a key, rate-limiting enzyme involved in polyunsaturated fatty acid (PUFA) metabolism. Recent studies suggest that changes in plasma PUFA levels can lead to disruptions in the neurotransmission system and increase the risk of mood disorders. FADS2 variations may contribute to the individual risk of developing bipolar disorder (BD). We investigated the association of regulatory FADS2 rs28456 with BD in the Turkish population. We performed TaqMan genotyping on 100 patients with BD and 91 healthy controls. Our results did not show significantly different genotype or allele frequencies of rs28456 in the BD cases compared to controls. However, we stratified the cases based on family history, which revealed that minor rs28456-G was observed more frequently (P=0.056) in cases without a family history of psychiatric illness compared to those with a family history of psychiatric illness. A marginally significant difference in the distribution of the “G” allele (P=0.053) between male patients and healthy males without a family history was observed. Our findings did not provide strong evidence supporting the reported association between rs28456 and BD, yet they point to its potential gender-specific effect, which requires further investigation. Future studies are necessary to explore the impact of FADS2 variations on BD risk in larger study groups, considering their potential interaction with non-inherited risk factors.